Glycosylated Biotherapeutics: Immunological Effects of N-Glycolylneuraminic Acid - Yehuda, Sharon; Padler-Karavani, Vered (Frontiers in Immunology, 2020)
The emerging field of biotherapeutics provides successful treatments for various diseases, yet immunogenicity and limited efficacy remain major concerns for many products. Glycosylation is a key factor determining the pharmacological properties of biotherapeutics, including their stability, solubility, bioavailability, pharmacokinetics, and immunogenicity. Hence, an increased attention is directed at optimizing the glycosylation properties of biotherapeutics. Currently, most biotherapeutics are produced in non-human mammalian cells in light of their ability to produce human-like glycosylation. However, most mammals produce the sialic acid N-glycolylneuraminic acid (Neu5Gc), while humans cannot due to a specific genetic defect. Humans consume Neu5Gc in their diet from mammalian derived foods (red meat and dairy) and produce polyclonal antibodies against diverse Neu5Gc-glycans. Moreover, Neu5Gc can metabolically incorporate into human cells and become presented on surface or secreted glycans, glycoproteins and glycolipids. Several studies in mice suggested that the combination of Neu5Gc-containing epitopes and anti-Neu5Gc antibodies could contribute to exacerbation of chronic inflammation-mediated diseases (e.g. cancer, cardiovascular diseases and autoimmunity). This could potentially become complicated with exposure to Neu5Gc-containing biotherapeutics, bio-devices or xenografts. Indeed, Neu5Gc can be found on various approved and marketed biotherapeutics. Here, we provide a perspective review on the possible consequences of Neu5Gc glycosylation of therapeutic protein drugs due to the limited published evidence of Neu5Gc glycosylation on marketed biotherapeutics and studies on their putative effects on immunogenicity, drug efficacy and safety.